Deep RNA Sequencing Reveals that MicroRNAs Play a Key Role in Lactation in Rats. Issue 8 (4th June 2014) - Zhang, ChunLei; Zhao, YuLong; Wang, YanHong; Wu, Hui; Fang, XingTang; Chen, Hong
Abstract: Understanding the regulatory contribution of maternal physiology to difficulties with lactation is beneficial to both mother and infant. MicroRNAs (miRNAs), a type of noncoding RNA, may be involved in the regulation of mammary gland development and function. In the present study, a deep RNA sequencing (RNA-seq) technique was used to compare the expression profile of miRNAs and mRNAs of 2 pooled RNA samples from day 1 and day 7 postpartum ( n = 1/d) rat ( Rattus norvegicus ) mammary glands to identify key miRNAs and their target genes that may control the rate-limiting steps of lactation. A total of 395 and 400 known miRNAs were identified in days 1 and 7 postpartum rat mammary samples, respectively. Compared with day 1 postpartum, 27 miRNAs were differentially expressed at day 7 postpartum. The expression differences between lactation periods were further analyzed by real-time quantitative polymerase chain reaction (qPCR) ( n = 5). The ΔΔCt values of rno-miR-30, rno-miR-1, rno-miR-145-3p, rno-miR-142, rno-miR-7a-5p, rno-miR-3571, rno-miR-224-5p, rno-miR-362-5p, rno-miR-342-3p, rno-miR-322-3p, rno-miR-18a-5p, and rno-miR-202-5p between the 2 libraries varied from 0.64 to 9.44; the ΔΔCt values of rno-miR-133, rno-miR-190a-5p, rno-miR-27a-5p, rno-miR-451-5p, rno-miR-3120, rno-miR-23a-5p, rno-miR-20a-3p, rno-miR-92a-1-5p, and rno-miR-134-5p between the 2 libraries varied from −1.02 to −4.37 ( P < 0.05). The intersection of the expressed mRNA genes from RNA-seq and putative target genes of differentially expressed miRNAs, termed mammary gland target genes (MTGs), was analyzed. The results indicated that 1259 MTGs overlapped between the 2 gene sets. The expression of 14 randomly selected genes of the MTGs was further confirmed by real-time qPCR ( R 2 = 0.86, P < 0.01). The downregulated MTGs were enriched for the pathways involved in lipid biosynthesis. This gene cluster included 24 lipid metabolic process–related genes, which were putative targets of 10 differentially expressed miRNAs. These results will be helpful in discovering the biologic underpinnings of poor lactation performance in women attempting to breastfeed.